2008
DOI: 10.1073/pnas.0800909105
|View full text |Cite
|
Sign up to set email alerts
|

Intraplastidial trafficking of a phage-type RNA polymerase is mediated by a thylakoid RING-H2 protein

Abstract: The plastid genome of dicotyledonous plants is transcribed by three different RNA polymerases; an eubacterial-type enzyme, PEP; and two phage-type enzymes, RPOTp and RPOTmp. RPOTp plays an important role in chloroplast transcription, biogenesis, and mesophyll cell proliferation. RPOTmp fulfills a specific function in the transcription of the rrn operon in proplasts/amyloplasts during seed imbibition/germination and a more general function in chloroplasts during later developmental stages. In chloroplasts, RPOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…Switching between the ''core DNA'' conformation and the ''surrounding DNA'' conformation could be mediated by chromatin remodeling proteins like SWIB-4 that are depicted here exemplarily at the interface between the two layers. Other membrane-associated proteins like the NEP interacting protein NIP can selectively control the activity of the NEP polymerase by preventing its association with plastid DNA (Azevedo et al 2008) an according classification has been discussed (Dillon and Dorman 2010). In this review we follow a simplified classification into enzymatic ptNAPs (including transcription, post-transcriptional levels of gene expression, DNA replication and repair) and architectural ptNAPs (including membrane anchoring and DNA compaction).…”
Section: Analysis Of the Protein Composition Of Plastid Nucleoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching between the ''core DNA'' conformation and the ''surrounding DNA'' conformation could be mediated by chromatin remodeling proteins like SWIB-4 that are depicted here exemplarily at the interface between the two layers. Other membrane-associated proteins like the NEP interacting protein NIP can selectively control the activity of the NEP polymerase by preventing its association with plastid DNA (Azevedo et al 2008) an according classification has been discussed (Dillon and Dorman 2010). In this review we follow a simplified classification into enzymatic ptNAPs (including transcription, post-transcriptional levels of gene expression, DNA replication and repair) and architectural ptNAPs (including membrane anchoring and DNA compaction).…”
Section: Analysis Of the Protein Composition Of Plastid Nucleoidsmentioning
confidence: 99%
“…On the other hand, at least one type of plastid RNA polymerase, namely the NEP encoded by the RPOTmp gene seems to be sensitive to membrane binding and was proposed to be switched off when it is brought into close proximity of the thylakoid membranes. This sensitivity might be conferred by a thylakoid membrane-embedded RING protein, NIP1 (NEP interacting protein 1), that showed specific interaction with RPOTmp (Azevedo et al 2008), reflecting the complex interplay between structure, distribution and activity.…”
Section: Sub-nucleoid Domainsmentioning
confidence: 99%
“…A model proposes that AthATL25/NIP2 accumulates and attaches to the membrane during light-dependent differentiation when the thylakoid membranes are assembled. 41 weigelworld.org/expviz/expviz.jsp), suggesting that it may be a pseudogene, or that its expression is highly specific.…”
Section: Athatl25/nip2 Mediates the Intraplastidial Trafficking Of Rpmentioning
confidence: 99%
“…RPOTmp is present in plastids and mitochondria of eudicotyledonous plants, and has been found to be soluble in nonphotosynthetic cells, but associates with thylakoid membranes of chloroplasts. 40 NEP-Interacting Protein 2 (NIP2) was identified in a yeast two-hybrid screen from a study searching for proteins that may assist in the association of RPOTmp with the thylakoid membrane 41 ; NIP2 corresponds to AthATL25. A series of biochemical tests led to the identification of AthATL25/NIP2 is an integral protein of the thylakoid membrane, which may localize to the stromal side.…”
Section: Athatl25/nip2 Mediates the Intraplastidial Trafficking Of Rpmentioning
confidence: 99%
“…This includes both nuclear-encoded polymerase and plastidencoded polymerase machinery. Plastidic RNA polymerase sigma (sig) factors are required as transcription factors for chloroplast genes with the loss of sig2 and sig6 delaying chloroplast biogenesis (Ishizaki et al, 2005;Chi et al, 2010) and nuclear-encoded RNA polymerases, such as rpoT, has been shown to affect chloroplast biogenesis (Azevedo et al, 2008).…”
Section: Chloroplast Gene Transcription and Translationmentioning
confidence: 99%